Burnout levels, work engagement and job satisfaction in social organisations in Portugal - Ricardo Pocinho; Rui Santos; Cristóvão Margarido; Sílvia Silva; Sara Gordo (EduSer)
Burnout has repercussions on job satisfaction. Therefore, this investigation aimed to analyze the relationship between burnout, work engagement and coping strategies of social workers in Portugal through the evaluation of 339 professionals, across an online questionnaire, regardless of the target population of their services and social responses. The main results demonstrate that professionals who recognize support from their managers, who feel integrated into their teams, who are satisfied with their life and professional roles and consider their physical and mental health to be positive, present lower levels of burnout, higher levels of commitment and use coping strategies to solve problems in their professional context. Higher burnout levels and lower work engagement were observed in professionals working in shifts, particularly in the night shift. Burnout symptoms are evidenced by physical fatigue, followed by cognitive fatigue, and emotional exhaustion. Regarding work engagement, the results obtained demonstrated high levels of professional engagement (78.3%). Working in Social Organizations is highly demanding and challenging. Consequently, there is an urgent need to develop educational programs aimed at training professionals in these settings. Such programs serve as a crucial protective factor against demotivation, thereby preventing emotional and physical exhaustion within the professional sphere.